A flexible Cellulose/Methylcellulose gel polymer electrolyte endowing superior Li+ conducting property for lithium ion battery. (15th October 2020) - Yu, Feng; Zhang, Hongbing; Zhao, Lingzhu; Sun, Zhipeng; Li, Yuli; Mo, Yan; Chen, Yong
Highlights: A flexible and thermostable GPE was formed via simple UV curing. GPE possessed the high ionic conductivity and ion transference number. The assemble cell owned good cycle performance. Abstract: With the advent of gel polymer electrolyte (GPE), a series of safety problems of lithium ion batteries have been resolved. However, poor self-standing property, the low ionic conductivity and Li + transference number are still the obstacles that impede the practical application of GPE. Herein, a flexible and eco-friendly GPE is designed using allyl-modified cellulose with methylcellulose through simple UV curing. The crosslinked structure facilitates the integrity of GPE during use, and methylcellulose guarantees the high affinity to liquid electrolyte and improve interfacial compatibility. The specific polar functional groups (OH, OCH3 and COC) in GPE cooperate to enhance the lithium salt dissociation, anion immobilization and lithium ion transporting and enable the high Li + transference number (0.902) and ion conductivity (4.36 × 10 -3 S cm -1 ). The assembled Li/GPE/LiFePO4 coin cells possess high initial discharge capacity of 150.6 mA h g -1 and a high capacity retention of 91.6 % after 100 cycles.